HUBUNGAN GAWAT JANIN, PREEKLAMSIA DAN DISPROPORSI KEPALA PANGGUL (DKP) DENGAN KEJADIAN SECTION CAESAREA - putri mayang sari; Chairuna; Sendy Pratiwi Rahmadhani (Poltekkes Kemenkes Medan, 2022)
A cesarean section can be important in situations of prolonged or obstructed labour, fetal distress, or because the baby is in an abnormal position but as with all surgeries, there can be risks. The purpose of this study was to determine the relationship between fetal distress, preeclampsia and head-pelvic disproportion (DKP) simultaneously with the incidence of Sectio Caesarea at DKT Lahat Hospital in 2020. The research method in this study was a quantitative research type of analytical survey research using a cross sectional approach. Sampling with systematic random sampling technique. This study uses secondary data with a population of 1418 respondent and the number of samples in this study were 93 respondents. The results of the univariate analysis of respondents who experienced caesarean section were 65 respondents (69.9%), 55 respondents experienced fetal distress (59.1%), 58 respondents experienced preeclampsia (62.4%), 62 respondents experienced Pelvic Head Disproportion (DKP) (66.7%). The results of the bivariate analysis showed that there was a significant relationship between Fetal Emergency with the incidence of Section Caesarea with p value of 0.000 < 0.05, Preeclampsia with the insidence of Section Caesarea p value of 0.001 < 0.05 and head and pelvis disproportion (DKP) with p value of 0.000 < 0,05 simultaneously with the insidence of low birth weight at the DKT Lahat Hospital in 2020. The conclusion of this study is that there is a relationship between fetal distress, preeclampsia and head-pelvic disproportion (DKP) simultaneously with the incidence of Sectio Caesarea at the DKT Lahat Hospital in 2020. As for suggestion For health workers, the results of this study are expected that health workers at the DKT Lahat Hospital can be alert to provide information and education to pregnant women regarding their pregnancy.